Middle School Principal Perceptions of Obstacles to Implementing Standards-Based Grading - Bauer, Steven Patrick (Southwest Baptist University, 2015)
Standards-based education has been cited for decades as a means to increasing student achievement. Standards-based grading (SBG) has been identified as a possible method to support learning of standards. While SBG has received much attention it is still a relatively uncommon practice in most schools. This quantitative study attempted to identify Missouri middle school principal perceptions of obstacles to implementing SBG. A survey of obstacles to implementing SBG which supported the scales of the study, instructional foundation, culture and climate, and resources was not located. Therefore, the researcher developed a survey to support the study goals. One of the study outcomes was the development of a valid and reliable survey instrument. Factor analysis and Cronbach’s alpha were utilized to establish the results were valid and reliable. The population size was 379 Missouri middle school principals. The final study data reached a sample size of 175. Statistically significant differences were found in six areas. Most notably there was a difference in perceptions of obstacles on the instructional foundation scale and the culture and climate scale for schools implementing SBG for 1 – 3 years compared to those not implementing SBG. The study did not examine the impact of SBG on achievement on high stakes testing, attendance, retention, and graduation rates. A study of achievement outcomes in schools currently implementing SBG is recommended. Studying student, parent, and teacher perception of culture and climate in SBG schools is also recommended.